1974
DOI: 10.1172/jci107861
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transient Efflux of Phosphate Ions from Pancreatic Islets as an Early Action of Insulin Secretagogues

Abstract: A B S T R A C T Anionic fluxes during the membrane realignments of stimulated insulin release have not been characterized previously although cations have been implicated in stimulus-secretion coupling. We have shown that a limited packet pulse of phosphate release ("phosphate flush") begins at the same time that the first phase of insulin secretion may occur. To demonstrate this phenomenon, we have prelabeled islets, obtained from rat pancreas by collagenase digestions, by incubation with [8'P]orthophosphate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 38 publications
7
59
0
Order By: Relevance
“…On the basis of the difference in profiles of [3H] Ad and45Ca release induced by two types of stimulation, that is, one with16.7 mM glucose and the other with slowly rising concentration of glucose, we now propose the same hypothesis as Freinkel et al(1974) have already described, which suggested that the discharge of ion or some substances might be caused by the alteration of the membrane permeability induced by an absolute change of the glucose concentration.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…On the basis of the difference in profiles of [3H] Ad and45Ca release induced by two types of stimulation, that is, one with16.7 mM glucose and the other with slowly rising concentration of glucose, we now propose the same hypothesis as Freinkel et al(1974) have already described, which suggested that the discharge of ion or some substances might be caused by the alteration of the membrane permeability induced by an absolute change of the glucose concentration.…”
Section: Resultssupporting
confidence: 52%
“…Freinkel et al(1974) indicated that Dglucose stimulated a rapid pulse of [32P] concomitant with insulin release of the first phase and suggested that this pulse of [32P] phosphate was associated with the excitatory state of the B cell produced by D-glucose. We further suggested that the release of [32P] phosphate might be caused via the glucoreceptor mechanism (Tsumura et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no direct linear relationship between enhanced phospholipid labelling and insulin secretion of pancreatic islets in response to glucose, experiments were made to test the effect on phospholipid synthesis of adding tetracaine, an antagonist of insulin secretion [13]. This local anaesthetic caused a pronounced increase in CDP diglyceride, phosphatidylglycerol and phosphatidic acid labelling and a reduction in phosphatidylinositol formation.…”
mentioning
confidence: 99%
“…It has been reported [3] that a transient 32p efflux from prelabelled pancreatic islets occurs as an early and highly specific response to glucose or other [4], and that it is impaired by starvation [6].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the role of anions in the secretory process of these hormones has received less attention [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%